Value-added Tea (Camellia sinesis) as a Functional Food using the Kombucha ‘Tea Fungus’ - Mindani I. Watawana (Science Faculty of Chiang Mai University, 2019)
The objective of this study was to determine the antioxidant and starch hydrolase inhibitory activities of Chinese black tea, oolong tea, green tea and Sri Lankan black tea through fermentation with the ‘tea fungus’ (Kombucha). The fermentation was carried out for 7 days and the functional properties were evaluated along with the pH, titratable acidity (TA) and color. The pH decreased significantly (P <0.05) from day 1 throughout the fermentation as compared with the unfermented teas. A statistically significant increase (P <0.05) of the TA was observed from day 5 onwards. The color of all four teas were observed to get lighter. Sri Lankan black tea and green tea had statistically significant increases (P <0.05) in the total phenolics content and antioxidant activities from day 1 along with the fermentation. This was further supported by the increases in the polyphenol contents in all fermented teas. All four fermented teas inhibited a-amylase better than a-glucosidase. Overall, Sri Lankan black tea was observed to be a better substrate than other examined in this paper for the preparation of Kombucha tea in view of its comparatively superior functional properties.